Medication Adherence in Comorbid Hypertension and Diabetes: An Exploratory Descriptive Qualitative Study of Healthcare Providers' Perspectives - Adwoa Oforiwaa Kwakye; Richard Delali Agbeko Djochie; Ama Agyeman‐Dua; Irene A. Kretchy (Health Science Reports, 2026)
ABSTRACT Background and Aims Medication adherence is a critical determinant of clinical outcomes among patients with comorbid hypertension and diabetes mellitus. Despite the availability of effective therapies, adherence remains suboptimal, particularly in low‐ and middle‐income settings where multiple patient, treatment, and health system factors influence medication‐taking behavior. Healthcare providers are uniquely positioned to identify barriers and facilitators to adherence. This study explored healthcare providers' perspectives on medication adherence among patients with comorbid hypertension and diabetes using the World Health Organization multidimensional adherence framework. Methods An exploratory descriptive qualitative study was conducted at the Pentecost Hospital, Ghana, between March and May 2025. Fifteen healthcare providers involved in the management of patients with hypertension and diabetes were purposively sampled, including medical officers, nurses, pharmacist, pharmacy technicians, dietitians, physician assistants, and mental health practitioners. Data were collected through semi‐structured in‐depth interviews lasting 30–60 min and analyzed using thematic analysis following Braun and Clarke's six‐step framework. Results Among the 15 participants, 53.3% ( n = 8) were female, 80.0% ( n = 12) aged 30–39 years, and 73.3% ( n = 11) had 1–6 years of professional experience. Five major themes were identified: patient‐related, therapy‐related, condition‐related, socio‐economic, and healthcare system‐related factors. Key barriers included forgetfulness, intentional dose modification, symptom‐driven discontinuation, cultural and religious beliefs about medicines, polypharmacy, medication side effects, fear of complications, anxiety, and medication costs. Facilitators included reminder systems, family and carer support, patient education, and multidisciplinary collaborative care. Participants emphasized the importance of integrating mental health services into chronic disease management. Conclusion Healthcare providers perceived medication adherence as influenced by interacting patient, therapy, condition, socio‐economic, and healthcare system factors. Interventions integrating patient education, family involvement, mental health support, and multidisciplinary care may support medication adherence and improve long‐term clinical outcomes.